Problematic Internet Use, Psychological Distress, and Quality of Life: A Study Among Greek Adults - Theodoratou, Maria; Katsarou, Dimitra; Varvitsioti, Maria; Efthymiou, Efthymia; Kougioumtzis, Georgios A.; Sofologi, Maria; Papadopoulou, Soultana (International Conference on Business and Economics - Hellenic Open University, 2025)
Problematic Internet Use (PIU) has emerged as a critical public health concern in the digital age, characterized by compulsive and excessive engagement with online activities that disrupt daily functioning and well-being. This study investigates the relationship between PIU, psychological distress, and quality of life, focusing on demographic and social factors influencing its prevalence. Findings reveal that younger adults and individuals with pre existing health conditions are particularly vulnerable to PIU, which exacerbates psychological distress, including symptoms of anxiety, depression, and emotional instability. The study highlights the detrimental impact of PIU on social relationships, as excessive internet use isolates individuals from meaningful offline interactions, reducing life satisfaction. Conversely, family status, particularly marriage, was identified as a protective factor, mitigating PIU and its associated psychological consequences through the stabilizing effects of social support and structured offline relationships. The findings underscore the importance of targeted interventions, such as cognitive-behavioral therapy (CBT), psychoeducation, and family-based approaches, to reduce PIU and promote mental health. This study contributes to a deeper understanding of PIU’s multifaceted nature and emphasizes the need for demographic-specific prevention strategies to address its adverse effects on mental health and quality of life. Future research should explore the long-term efficacy of interventions and the role of emerging digital trends in shaping PIU behaviors. JEL Classifications: I31, D83 Keywords: Problematic Internet Use (PIU), Psychological Distress, Quality of Life, Digital Addiction, Interventions